MIN in Rural and Urban Areas: Implementation of Talking Stick Learning Model in Al-Qur’an Hadith Subject - Alimni Alimni; Alfauzan Amin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The purpose of this study was to determine differences in the tolerance character of students by applying the talking stick MIN model in Bengkulu Selatan district and MIN students in Bengkulu city. This type of research was mixed-method research using an explanatory design. The sampling technique in this study was total sampling. Collecting data in this study used a tolerance character questionnaire distributed to students from class IV MIN 1 Bengkulu City, class IV MIN 2 Bengkulu City students, grade IV students of MIN 1 South Bengkulu Regency MIN 2 South Bengkulu Regency, which totaled 100 students. Data analysis used the Independent Samples T-test and descriptive statistics. The results of this study indicated that the sig (2-tailed) Independent T-test value is 0.162 ≥0.05, so Ho was accepted, and Ha was rejected, meaning that there was no significant difference between the average scores of students' tolerance character in MIN Bengkulu Selatan Regency (rural area area) and MIN Kota Bengkulu (Urban area area) where both schools implemented cooperative learning model of talking stick type in Al-Qur'an Hadith subject. Based on the results of interviews, after applying the talking stick model, students felt happy and excited while learning because learning was not dull, so that students also more easily understood the learning materials presented by the teacher.